2005
DOI: 10.1007/bf03347567
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neurosurgical outcome in pituitary tumors

Abstract: PRL secretion, tumor size and operation date are the main predictors of neurosurgical outcome in pituitary tumors, the latter suggesting that neurosurgical experience plays an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Although GTR is not always possible, a variety of surgical tools have been introduced in transsphenoidal surgery in the last 2 decades in order incrementally to improve the degree of tumor resection. 1,4,17,18,24 The endoscope has become widely adopted in academic skull base centers to provide greater illumination of endonasal skull base structures and angled viewing, both of which are often suboptimal with a traditional microscopic view. Although most surgeons would agree that a better view should increase the potential for GTR and therefore improve clinical outcomes, this is speculative and has not been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Although GTR is not always possible, a variety of surgical tools have been introduced in transsphenoidal surgery in the last 2 decades in order incrementally to improve the degree of tumor resection. 1,4,17,18,24 The endoscope has become widely adopted in academic skull base centers to provide greater illumination of endonasal skull base structures and angled viewing, both of which are often suboptimal with a traditional microscopic view. Although most surgeons would agree that a better view should increase the potential for GTR and therefore improve clinical outcomes, this is speculative and has not been proven.…”
Section: Discussionmentioning
confidence: 99%
“…It allows decompression of the optimal neural structure and chances for endocrinopathy reversal. 6,[11][12][13][14][15] Although little direct evidence shows that the maximal extent of resection minimizes the risk of recurrence, the size of the original tumor has been significantly correlated to tumor recurrence. Larger tumors correlate with a higher chance of postoperative residual tumor, [16][17][18][19][20] and a higher recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the original tumor has been significantly correlated to tumor recurrence; this finding indicates that larger tumors correlate with higher chances of postopera- tive residual tumor. 2,4,12,13,27,28 The size of a residual tumor has been shown to be an independent predictor of the response to adjuvant radiation treatment, with higher remission rates for smaller lesions and radiation fields. 19,42 The minimization of residual tumor has also been associated with a delay in adjuvant radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,9,10,17,21,29,31,43,44 Because of the growth pattern of macroadenomas with extensions out of the surgeon's direct view through the transsphenoidal corridor, several authors have reported surprisingly high percentages of unexpected residual tumor based on intraoperative and postoperative MR imaging. 3,14,15,33,37,38 Despite its proven potential for decreasing the rates of unexpected tumor residuals, iMR imaging is infrequently used, even in the few operating environments in which such technology is available.…”
mentioning
confidence: 99%